2017
DOI: 10.3349/ymj.2017.58.5.1006
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Association between Lysyl Oxidase Gene Polymorphism and Intracranial Aneurysm in Koreans

Abstract: PurposeLysyl oxidase (LOX) controls the cross-linking and maturation of elastin and collagen fibers. In this study, we investigated the association between LOX gene polymorphisms and intracranial aneurysm (IA) formation in a homogeneous Korean population.Materials and MethodsThis cross-sectional study involved 80 age-sex matched patients with IA and controls. Fisher's exact test was performed to analyze allelic associations between ten single nucleotide polymorphisms (SNPs) and IA, including 41 ruptured and 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…Non-saccular aneurysms, such as fusiform, dissection, traumatic, and infectious aneurysms, as well as familial aneurysms were excluded. Control subjects met the following criteria: 1) they underwent computed tomography or magnetic resonance angiography for headache evaluation or medical check-up; 2) had no concomitant neurological diseases, such as arteriovenous malformation, intracranial hemorrhage, or infarct; 3) had no familial history of IA or SAH in first-degree relatives; 4) had neither Parkinson’s disease (PD) or Alzheimer’s disease; and 5) were over 18 years of age [17,18]. Finally, this prospective study included radiologically confirmed IA with saccular shape ( n = 250) and 296 controls enrolled from March 2015 to May 2018 at a single institution.…”
Section: Methodsmentioning
confidence: 99%
“…Non-saccular aneurysms, such as fusiform, dissection, traumatic, and infectious aneurysms, as well as familial aneurysms were excluded. Control subjects met the following criteria: 1) they underwent computed tomography or magnetic resonance angiography for headache evaluation or medical check-up; 2) had no concomitant neurological diseases, such as arteriovenous malformation, intracranial hemorrhage, or infarct; 3) had no familial history of IA or SAH in first-degree relatives; 4) had neither Parkinson’s disease (PD) or Alzheimer’s disease; and 5) were over 18 years of age [17,18]. Finally, this prospective study included radiologically confirmed IA with saccular shape ( n = 250) and 296 controls enrolled from March 2015 to May 2018 at a single institution.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the elastin gene, patients harboring the T allele of rs2856728 demonstrated a statistically significant association with IA, particularly in males (OR, 3.45 in males vs. 1.88 in females) [ 16 ]. Among the lysyl oxidase SNPs, rs2303656, rs3900446, and rs763497 increased IA risk significantly [ 11 ]. A recent GWAS revealed eight new susceptibility loci, including GBA , TCF24 , OLFML2A , ARHGAP32 , CD163L1 , CUL4A , LOC102724084 , and LRRC3 , that had statistical power over 0.8 in Korean IA patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of homogeneous, Korean population researchers investigated the association between IA formation and LOX gene polymorphisms. [ 17 ] Authors studied ten single-nucleotide polymorphisms (SNPs), of which three SNPs were identified which plays a significant role in the formation of IA ( P < 0.01).…”
Section: Discussionmentioning
confidence: 99%